Evaluation of E-Government Implementation in Managing Public Service Complaints Using E-GovQual and Importance Performance Analysis (Case Study: CRM - Cepat Respon Masyarakat – of the Jakarta Provincial Government) - Sabri Alim; Habibullah Akbar; Gerry Firmansyah; Nenden Siti Fatonah; Budi Tjahjono (CCIT (Creative Communication and Innovative Technology) Journal, 2024)
The improvement of public service quality is an effort to enhance the quality and innovation of public services within each government agency periodically, according to the needs and expectations of the society. One of the efforts to enhance the quality of service by public service providers, in order to improve the well-being of the community, is to use public complaints as a basis for making improvements in public services. According to data from the Central Bureau of Statistics in 2022, the population of DKI Jakarta is 10,679,000. The Provincial Government of DKI Jakarta has an integrated complaint system called "Cepat Respon Masyarakat" (CRM), which serves as a platform for the public to report issues within the DKI Jakarta area. The assessment of the "Cepat Respon Masyarakat" system is necessary to ensure that the services provided through the system can be utilized by the public and to obtain feedback regarding aspects that need improvement by the DKI Jakarta Provincial Government, which serves as the service provider. The purpose of this research is to determine the quality of the "Cepat Respon Masyarakat" complaint system using the e-GovQual method and identify attributes that require priority for service quality improvement using Importance Performance Analysis. In this study, 6 dimensions and 21 e-GovQual attributes are used to assess service quality with a sample of 118 respondents. The analysis results indicate a level of conformity of 98.39% (<100%) for the 6 dimensions, meaning that the public service provided through the "Cepat Respon Masyarakat" system still falls short of user expectations. The average gap (GAP) between expectations and performance is -0.03 or < 0, suggesting that, based on public perceptions, the quality of complaint service performance through the CRM system is still not up to par with expectations. The attributes that require improvement are those located in Quadrant A (1 attribute) and Quadrant C (7 attributes). Recommendations are provided based on literature/theory for attributes that need improvement to enhance the quality of complaint services in DKI Jakarta.